Implementation of Just in Time to Reduce Lead Time and Improve Production Efficiency: A Case Study at PT Toyota Boshoku Indonesia - Eman Rusmana; Adi Rusdi Widya; Christa Dian Pratiwi (Mandalika Institute, 2026)
This study aims to analyze and implement the Just In Time (JIT) method to reduce production lead time and improve production efficiency in the Headrest IMV production line at PT Toyota Boshoku Indonesia. The research employs an applied research approach using Value Stream Mapping (VSM) to identify inefficiencies and design process improvements. Data were collected through direct observation, interviews, documentation, and time studies to evaluate the current production condition and measure performance improvements after JIT implementation. The results indicate that the initial production system, which operated under a push-based approach, experienced significant inefficiencies, including high waiting time, excessive Work In Process (WIP), and unbalanced workflow. After implementing JIT, production time per unit decreased from 13.2 minutes to 9.5 minutes, representing a 28% improvement. In addition, WIP levels were significantly reduced, and the production system transitioned into a pull-based system supported by Kanban. Layout redesign and work standardization further enhanced material flow and process stability. The implementation results also demonstrated improvements in key performance indicators, including reduced production lead time, shorter cycle time, lower WIP levels, and increased overall production efficiency. In conclusion, the implementation of JIT integrated with VSM effectively reduces production lead time, minimizes waste, and improves overall production efficiency. This study provides practical and empirical insights into the application of Lean Manufacturing principles in real industrial settings.